Megjegyzések a magyar bankok Trianon utáni reálgazdasági aktivitásának kérdéséhez - Baracsi, Lóránt (Közép-Európai Közlemények, 2019)
According to Rudolf Hilferding the funding of real economy (industry, commerce, agriculture) by banks and the domination of banks over industrial capital evolved thus is an accompany of modern capitalism; conversely, Alexander Gerschenkron, on the basis of economic development of European countries, especially of Germany and Austro-Hungarian Monarchy argued that this phenomenon is related with economic backwardness and the “credit mobilier” banks played an important role in the development of economically backward countries. Although the recent researches in the main questioned these theories (e.g. the large banks not undertaken in the least to encourage and establish innovations, “startups”, risky investments, rather they financed a narrower group of established, stable companies, gave “development assistance for the strong”), may arise if they could be acceptable with reference to the economic development of Hungary. Before the First World War in Hungary gave the impression of bank domination the fact that members of some bank’s management were simultaneously members of board of directors of many companies in real economy (above all from the Hungarian General Credit Bank and the Hungarian Commercial Bank of Pest). However, there is little evidence of banks domination of industrial companies’ activities, the actually measures of relations between these entities (lending, respectively founding or strategy ownership) was not significant, from nor the banks and nor the companies point of view. In our issue we examine if had been modified significantly participation, influence of banks in funding of real economy after Treaty of Trianon.